Role of Community in Increasing Interest in Sports in Indonesian Society - Ba'Zandya, Fakhren Daifullah; Hakim, Arif; Sismi, David Ziyan Fuadi Salim; Setiawan, Muhammad Arief (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This study highlights role of community sport in increasing interest exercise among Indonesian society, which until now still own level participation low. Based on the 2021 National Sports Development Index (SDI) data, only 5.86% of the population has condition prime physical condition, while 76% are classified as No healthy. Factors that cause low participation sports covering busyness, lack of facility sports, low awareness, as well as lack of motivation individuals to make sport as part from style life. This study uses a approach qualitative, with data collection through interviews deep with the administrator of community sports, members, and stakeholders interested in others. Research results show that community sport's own role is important in providing supporting facilities, organizing activity interesting sport, as well as giving education that improves awareness will importance sports for health physical and mental. In addition, the interaction social that is woven into community participate push individuals to participate active in active sports routinely This study also emphasizes the importance of collaboration between the community, government and sectors private sector to create supportive policies development of community sports in a way comprehensive. Steps strategic needs done cover the provision facility equitable and affordable sports, improving education programs health, as well as funding activity community. With the development of community, inclusive, sustainable and collaborative sports expected participation public in active sports can increase, so that created a more society healthy, active, and productive.